The Zoutsteeg Three: Three New Cases of African Types of Dental Modification from Saint Martin, Dutch Caribbean. (29th June 2012) - Schroeder, H.; Haviser, J. B.; Price, T. D.
ABSTRACT Dental modification was widely practiced in sub‐Saharan Africa as a form of cultural expression, and during the era of the transatlantic slave trade, it was regularly identified in enslaved Africans who were transported to the Americas. Here, we report three new cases of African types of dental modification from the Caribbean island of Saint Martin that were recently encountered during construction activities in the Zoutsteeg area of Philipsburg, the capital of the Dutch half of the island. The artifacts associated with the burials indicate that they date to the late 17th century, prior to the foundation of the town of Philipsburg in 1735. The dental evidence further suggests that the three individuals were born in Africa, as opposed to the Americas. This could be confirmed by tooth enamel strontium isotope measurements which yielded values that are inconsistent with an origin in the Caribbean but consistent with an origin in Africa. Unfortunately, neither the dental patterns nor the strontium isotope values allow us to determine their specific origins in Africa. However, both the methods used to modify the teeth and the isotope ratios suggest that the 'Zoutsteeg Three' originated in different parts of Africa. Copyright © 2012 John Wiley & Sons, Ltd.